Dawn of nitride ferroelectric semiconductors: from materials to devices. (6th March 2023) - Wang, Ping; Wang, Ding; Mondal, Shubham; Hu, Mingtao; Liu, Jiangnan; Mi, Zetian
Abstract: III-nitride semiconductors are promising optoelectronic and electronic materials and have been extensively investigated in the past decades. New functionalities, such as ferroelectricity, ferromagnetism, and superconductivity, have been implanted into III-nitrides to expand their capability in next-generation semiconductor and quantum technologies. The recent experimental demonstration of ferroelectricity in nitride materials, including ScAl(Ga)N, boron-substituted AlN, and hexagonal BN, has inspired tremendous research interest. Due to the large remnant polarization, high breakdown field, high Curie temperature, and significantly enhanced piezoelectric, linear and nonlinear optical properties, nitride ferroelectric semiconductors have enabled a wealth of applications in electronic, ferroelectronic, acoustoelectronic, optoelectronic, and quantum devices and systems. In this review, the development of nitride ferroelectric semiconductors from materials to devices is discussed. While expounding on the unique advantages and outstanding achievements of nitride ferroelectrics, the existing challenges and promising prospects have been also discussed.